2009
DOI: 10.1007/s00221-009-1751-3
|View full text |Cite
|
Sign up to set email alerts
|

Different neural strategies for multimodal integration: comparison of two macaque monkey species

Abstract: The integration of neck proprioceptive and vestibular inputs underlies the generation of accurate postural and motor control. Recent studies have shown that central mechanisms underlying the integration of these sensory inputs differ across species. Notably, in rhesus monkey (macaca mulata), an Old World monkey, neurons in the vestibular nuclei are insensitive to passive stimulation of neck proprioceptors. In contrast, in squirrel monkey, a New World monkey, stimulation produces robust modulation. This has led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 41 publications
8
34
0
Order By: Relevance
“…In this way, VO neurons and PVP neurons in rhesus monkeys are comparable after lesion (compare with Sadeghi et al 2010). Similar findings have been reported in studies performed in the vestibular nuclei of normal cats (Kasper et al 1988), squirrel monkeys (Gdowski et al 2001), and cynomolgus monkeys (Sadeghi et al 2009). …”
Section: Functional Role For Unmasking Of Neck Proprioceptive Signalssupporting
confidence: 88%
See 3 more Smart Citations
“…In this way, VO neurons and PVP neurons in rhesus monkeys are comparable after lesion (compare with Sadeghi et al 2010). Similar findings have been reported in studies performed in the vestibular nuclei of normal cats (Kasper et al 1988), squirrel monkeys (Gdowski et al 2001), and cynomolgus monkeys (Sadeghi et al 2009). …”
Section: Functional Role For Unmasking Of Neck Proprioceptive Signalssupporting
confidence: 88%
“…As such, VO neurons are similar to VOR interneurons (i.e., PVP neurons) in that neck inputs are unmasked only after lesion (Sadeghi et al 2010). Interestingly, in both studies, the percentage of neck-sensitive neurons observed after lesion (ϳ50%) was comparable to that observed in normal conditions in other species (Gdowski et al 2001;Kasper et al 1988;Sadeghi et al 2009). We suggest that the acute appearance of neck proprioceptive signals in the vestibular nuclei neurons of rhesus monkeys after lesion reveals neck-vestibular connections that are present before lesion, but make silent synapses on vestibular nuclei neurons that become active only when vestibular inputs are decreased.…”
Section: Unmasking Of Neck Proprioceptive Signalssupporting
confidence: 80%
See 2 more Smart Citations
“…In fact, many of the moderately active NEM neurons also responded in phase with stimulus position, preferred pitch and roll rotations, and modulated their firing rate with tail movements. Whether these neurons are also related to postural responses is unknown; however, NEM cells in other species have often been associated with vestibulospinal pathways (McCrea et al, 1999;Boyle, 2001;Sadeghi et al, 2009).…”
Section: Neurons and State-dependent Behaviormentioning
confidence: 99%